PENERAPAN MIXTURE MODEL KEPADA APLIKASI HELPDESK BERBASIS WEB - Mira Chandra Kirana; Landong Moral Etisa (Computer Society of Nahdlatul Ulama (CSNU) Indonesia, 2017)
The use of mixture models in the application implementation helpdesk aims to find the spread of data from various data hordes in order to find data near the desired results. It aims to facilitate the search for information derived from the company's technical documents. The use of helpdesk applications is to manage complaint data or any problems that are owned by customers, thus requiring service providers. Because companies engaged in services have a number of customers who are not small and have different problems. As well as having customers in different locations - requiring customer data management that can store location data with ease to use, it is preferred to store customer's address data. For that helpdesk application also uses map mapping online by using google map.Purpose in order to present the data online and can be accessed wherever located.